Incidental Dural Tears in lumbar decompressive surgery: Incidence, causes, treatment, results. - Kalevski, S.K (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: Incidental dural tears or durotomy (ID) during lumbar decompressive surgery is a relatively rare complication causing severe consequences. Their incidence varies widely among different authors (1-17%) and in general depends on the type and complexity of the spinal procedures performed. With the present investigation the authors aim to evaluate the incidence of incidental durotomies during the different types of decompressive and reconstructive surgical procedures in the lumbar region, also indicating the most common reasons for incidental durotomies, treatment options and the early and remote outcome. MATERIAL AND METHODS: The records of 553 consecutive patients with different types of posterior and posterolateral decompressive and reconstructive procedures in the lumbar region are investigated retrospectively for the period January 2005 – march 2009. RESULTS: The overall incidence of the incidental durotomies in the investigated group is 12.66%. In the subgroups it varies depending on the specificity of the surgical procedures performed. The biggest is the number of IDs in the reoperative spinal surgery subgroup, followed by the subgroup of the patients who sustained spinal trauma, followed by those with degenerative spinal stenosis, tumors and lumbar disc herniations. CONCLUSION: IDs should be considered as a serious complication with a multitude of unwanted consequences for the patients. Prevention is the best way to treat the complications and disability that attend the unwanted dural tears. Knowing about the mechanisms and predisposing factors for that objectionable complication is a matter of utmost importance when planning and performing spinal surgical procedures.